SOSIALISASI “ISI PIRINGKU” SEBAGAI PENCEGAHAN STUNTING DI RAUDLATUL ATHFAL TANWIRUT TULAB PAYUNG MAKMUR LAMPUNG TENGAH - Ayu, Riska Nur Suci; Surahman, Novriansyah (EJOIN : Jurnal Pengabdian Masyarakat, 2023)
Stunting is a chronic condition resulting from nutritional deficiencies that can lead to toddlers having a stature/height shorter than their age would typically indicate. The prevention of stunting can be achieved through the provision of education and the implementation of nutritional fulfillment for children based on the "Isi Piringku" principle. " Isi Piringku" is a component of the recommendations for a healthy diet by fulfilling balanced nutrition that considers the quantity and types of food, including staple foods, animal-based dishes, plant-based dishes, vegetables, and fruits. The target of this socialization is the parents of 60 students. This activity is conducted at Raudlatul Athfal Tanwirut Tulab in the village of Payung Makmur, Central Lampung. The implementation process consists of two stages: the first stage involves delivering a presentation on the " Isi Piringku " concept, and the second stage includes a demonstration/practical session of food plating in accordance with the principles of " Isi Piringku." The outcome of this activity is that participants comprehend the content presented during the discussion session in the socialization stage, as evidenced by their enthusiasm in asking questions related to the conveyed material. As well as understanding the material, as demonstrated by the presentation of menu plating results following the principles of " Isi Piringku " during the demonstration/practical stage. The practical results indicate that the food plating practice conducted by 47 parents (78.3%) was appropriate, while 13 parents (16.7%) did not follow the guidelines. The conclusion drawn is that parents are capable of understanding the implementation of " Isi Piringku " to prevent stunting